Tata Kelola Perkotaan dan Ketahanan Ekonomi di Indonesia: Suatu Tinjauan Kualitatif - Susan Purnama; Fitriani Reyta; Bob Foster; Johnson Sinaga (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
Urban communities face various challenges, one of which is strengthening economic resilience. The aim of this research is to reveal the relationship between economic resilience and good urban governance in Indonesia, especially the City of Bandung in the field of credit distribution policy. The findings in this research were conceptualized using qualitative descriptions. Based on the findings obtained, the implementation of good urban governance in the field of corporate credit programs is still not optimal and further development of policies and supervision of fund distribution officers, channeling institutions and recipients of financial support is still needed. The managerial implications for the Bandung city government are increasing credit distribution to the productive sector, especially the service sector, adding collateral before credit distribution, and increasing credit risk mitigation for young debtors, medium freeze debtors (Rp. 10 - 20 million/month), and debtors subject to interest rates. higher interest.